A methodology to characterize bias and harmful stereotypes in natural language processing in Latin America - Alemany, Laura Alonso (2023)
Automated decision-making systems, specially those based on natural language processing, are pervasive in our lives. They are not only behind the internet search engines we use daily, but also take more critical roles: selecting candidates for a job, determining suspects of a crime, diagnosing autism and more. Such automated systems make errors, which may be harmful in many ways, be it because of the severity of the consequences (as in health issues) or because of the sheer number of people they affect. When errors made by an automated system affect a population more than other, we call the system biased.Most modern natural language technologies are based on artifacts obtained from enormous volumes of text using machine learning, namely language models and word embeddings. Since they are created applying subsymbolic machine learning, mostly artificial neural networks, they are opaque and practically uninterpretable by direct inspection, thus making it very difficult to audit them.In this paper we present a methodology that spells out how social scientists, domain experts, and machine learning experts can collaboratively explore biases and harmful stereotypes in word embeddings and large language models. Our methodology is based on the following principles:1. focus on the linguistic manifestations of discrimination on word embeddings and language models, not on the mathematical properties of the models2. reduce the technical barrier for discrimination experts3. characterize through a qualitative exploratory process in addition to ametric-based approach4. address mitigation as part of the training process, not as an after thought.